1992
DOI: 10.1080/00986449208936078
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Flow Over Periodic Surfaces

Abstract: Laminar flows confined between parallel surfaces, one of which is periodically "rough," are studied. The effect of surface roughness has been computed for both drag and pressure flows. A basis of comparison is defined so that the effect of roughness on the rate of flow parallel to the surfaces can be quantified. The external flow penetrates the roughness elements to a degree that depends upon the parameters that characterize the roughness. The presence of a pressure gradient exerts a strong influence on the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Figure 12 shows that the ow characteristics for the 'combined' inputs are intermediate between the individual Poiseuille and Couette ows over the cavity. The results in the present study show similar qualitative behaviour to those [14,15] for Stokes ow. It is worth mentioning that for Poiseuille ow oscillatory behaviour at Gr = 2000 is not observed until the values of Gr higher than 4000 [21].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Figure 12 shows that the ow characteristics for the 'combined' inputs are intermediate between the individual Poiseuille and Couette ows over the cavity. The results in the present study show similar qualitative behaviour to those [14,15] for Stokes ow. It is worth mentioning that for Poiseuille ow oscillatory behaviour at Gr = 2000 is not observed until the values of Gr higher than 4000 [21].…”
Section: Resultssupporting
confidence: 84%
“…It is obtained that the percentage of markers removed from a cavity increases with the increasing H=D, shown in Figure 10. O'Brien [14] and Mickaily et al [15] have studied the situation where a combination of Couette and Poiseuille ows is used under Stokes ow conditions. In this case, the upper wall moves at a velocity u from left to right and an existing Poiseuille ow acts in the same direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments on sedimentation of a steel cylinder through a viscous liquid (19) showed that the sedimentation velocity of a rough cylinder near the container wall could be twice as fast as that of a smooth cylinder. The magnitude of the effect depends on the ratio of the rough layer thickness to the gap width.…”
Section: Possible Effects Of Chains On the Accuracy Of Force Measuremmentioning
confidence: 99%
“…1 Couette flow is a steady, wall-driven flow that is one of the exact solutions of the Navier-Stokes equations. 3 The purpose of this facility is for comparison to external flows, where the Blasius profile is best characterized by Couette flow close to the wall. Much of the research to quantify the drag on patterned surfaces involves measuring the pressure drop occurring in a channel flow ͑typically one wall consisting of the patterned surface͒ such as that described by Rothstein; 2 however this is an indirect method.…”
Section: Introductionmentioning
confidence: 99%